Assessment of suitable envelope materials in multi-climate zones of India to construct an economical building. (11th October 2022) - Hasan, Shaheen; Khan, Sabah
The study is carried out for different climatic zones of India, by considering five different weather zones that are composite, cloudy, moderate, cold, and hot and dry. Basically Indian weather zones are described in six types of zones, but one is a mixed type, so for better understanding, the study carried out in five types of climate zones. This study shows an assessment of selected walling materials for building setups present in multi-weather zones of India. The analysis of building materials is done with the help of discrete parameter such as construction expenditure, energy consumption amount, life cycle cost, embodied energy, energy performance index, reduction of carbon emission, and payback period, etc. The wall material properties are identified for these locations as Case_I, Case_II, Case_III, Case_IV, and Case_V, for ease of calculation.